2018
DOI: 10.1016/j.jopan.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perceptions of Perioperative Quality of Care in Relation to Self-rated Health

Abstract: Nurses should chart patients' estimations of their physical health initially in care to provide reinforced support for patients who estimate their physical health is less than good. Before surgery, patients who have estimated their physical health as being less than good should be given realistic information about their stay in the PACU-that they will be in a PACU after surgery, what that stay means, and why it is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
(48 reference statements)
0
5
0
3
Order By: Relevance
“…However, those authors used a single instrument to assess the quality of perioperative care, evaluating the entire surgical hospital staff, not just the nursing team. 20 We found that patient satisfaction was associated with several different aspects, an awareness of which would allow hospitals to improve of quality services to better meet the needs of patients. For example, in line with previous studies, we found that men were more satisfied with nursing care than women.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, those authors used a single instrument to assess the quality of perioperative care, evaluating the entire surgical hospital staff, not just the nursing team. 20 We found that patient satisfaction was associated with several different aspects, an awareness of which would allow hospitals to improve of quality services to better meet the needs of patients. For example, in line with previous studies, we found that men were more satisfied with nursing care than women.…”
Section: Discussionmentioning
confidence: 87%
“…However, those authors used a single instrument to assess the quality of perioperative care, evaluating the entire surgical hospital staff, not just the nursing team. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los pacientes quirúrgicos ambulatorios refuerzan el valor de los elementos representados por la información y la comunicación. Los pacientes que consideran buena su salud están más satisfechos con la información recibida y con su oportunidad de participar en las decisiones sobre sus cuidados perioperatorios que aquellos que califican su percepción sobre su estado de salud menor que buena (243). Lemos et al detectaron que la información clínica era un factor que influenciaba la satisfacción de los pacientes ambulatorios quirúrgicos.…”
Section: Informaciónunclassified
“…En una publicación sueca que analiza a 170 pacientes adultos se observó que cuanto más detallada era la información que recibía el paciente mayor ansiedad desencadenaba (243). Sin embargo, en ensayos clínicos aleatorizados de niños que iban a ser intervenidos la información preoperatoria más detallada no resultó en un aumento de la ansiedad de los niños o los padres (246,247).…”
Section: Informaciónunclassified